Orientasi Studi Islam di Indonesia: Mengenal Pendidikan Kelas Internasional di Lingkungan PTAI - Khamami Zada (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Enthusiasm growth to comprehend the Islam more as â€œreligious tradition that existâ€, historical, compared to â€œset of doctrineâ€ in al-Qurâ€™an and Hadits, finding its momentum in growth of Islamic study in some notable and big university in United States. This then applied in religious Islam colleges. There also shift from more normative character of Islamic study to more historical, sociologic, and empiric one. Second, thereâ€™s tendency, broader scientific orientation. If at previously period scholar orientation tends to middle easterly, especially al-Azhar University, in the last two decade looked to be progressively wide of and immeasurable. Because that, nowadays started development of Islamic education instructing at demand of enhancing implementation quality, management, curriculum with the international standard. One of them is by opening international class (Islamic education), that expected can compete in global level..